The Impact of Oyster Mushrooms (Pleurotus ostreatus) on the Baking Quality of Rye Flour and Nutrition Composition and Antioxidant Potential of Rye Bread - Sylwia Stępniewska; Agnieszka Salamon; Grażyna Cacak-Pietrzak; Małgorzata Piecyk; Hanna Kowalska (Foods)
This study aimed to evaluate the use of oyster mushroom (Pleurotus ostreatus) powder (OMP) for producing rye bread. The raw materials were low-extract rye flour and OMP, which were analyzed in terms of their nutritional and health-promoting qualities. Mixtures of rye flour with OMP were prepared, replacing 5, 7.5, and 10% rye flour with OMP. The baking quality of the tested flour samples was assessed based on their water absorption, falling number, and amylograph and swelling curve tests. The laboratory baking test was carried out using the sourdough method, prepared based on LV2 starter cultures, and the bread samples were assessed in terms of their technological, sensory, and nutritional characteristics, as well as the antioxidant potential. The OMP was characterized by a high content of basic nutrition components and a higher antioxidant potential. The addition of OMP increased the nutritional value of the rye flour and its water absorption, significantly prolonged the starch gelatinization time, and increased the xylolytic activity of the flour. The OMP enhanced the bread’s dietary fiber, minerals, protein, and phenolic compounds, and boosted its antioxidant potential. Also, the starch present in the bread with OMP was characterized by a higher pro-health value due to a higher share of slowly digestible starch. Incorporating 7.5% OMP into the rye bread formula positively affected the bread’s sensory profile in contrast to the bread with a 10% addition of OMP.